(untitled) (Research, Society and Development, 2021)
Objective: To understand the safety culture found in the operating room. Methodology: This is an integrative literature review that used the PRISMA methodology as a guide in publications over the last five years (2015 to 2020) in the MEDLINE, PUBMED, LILACS and BDENF - Nursing in English, Portuguese, Spanish and texts available in full. To extract data from the articles, an instrument was developed containing the following variants: title, author, year, database, crossing of descriptors, period, type of study, population, sample, study site, safety adherence, evaluation of patient safety, study contribution to the health team. Results: Five articles were selected after exclusion due to escape from the topic, unavailability of the full text and that answered the guiding question: “What is the safety culture present in the operating room?”. After careful analysis, it was observed that the safety culture in the surgical environment is considered a key element to reduce adverse events and aims to ensure that surgical teams develop safety protocols critically. Conclusion: Health institutions increasingly use the evaluation of the safety culture as a strategy to ensure quality care, with the absence of errors and adverse events.